Genetic Variants in TNFSF4 and TNFSF8 Are Associated With the Risk of HCV Infection Among Chinese High-Risk Population - Fu, Zuqiang; Cai, Weihua; Shao, Jianguo; Xue, Hong; Ge, Zhijun; Fan, Haozhi; Dong, Chen; Wang, Chunhui; Zhang, Jinwei; Shen, Chao; Zhang, Yun; Huang, Peng; et al. (Frontiers in Genetics, 2021)
Background: The tumor necrosis factor superfamily (TNFSF) and TNF receptor superfamily (TNFRSF) play important roles in the immune responses to infections. The aim of this study was to determine the impact of single nucleotide polymorphisms (SNPs) of several TNFSF/TNFRSF genes on the risk of hepatitis C virus (HCV) infection in the Chinese high-risk population. Methods: The TNFSF4-rs1234313, TNFSF4-rs7514229, TNFSF8-rs3181366, TNFSF8-rs2295800, TNFRSF8-rs2298209 and TNFRSF8-rs2230625 SNPs were genotyped in 2309 uninfected controls, 597 subjects with spontaneous HCV clearance and 784 patients with persistent HCV infection using the TaqMan-MGB assay. The putative functions of the positive SNPs were determined using online bioinformatics tools. Results: After adjusting for gender, age, high-risk population, alanine transaminase (ALT), aspartate aminotransferase (AST), IL28B-rs12979860 and rs8099917 genotypes, the non-conditional logistic regression showed that rs7514229-T, rs3181366-T and rs2295800-C were associated with an increased risk of HCV infection (all PFDR<0.05). Combined analysis of rs7514229-T and rs3181366-T risk alleles showed that the subjects carrying 2-4 risk alleles were more susceptible to HCV infection compared to those lacking any risk allele (all P<0.001). Furthermore, the risk of HCV infection increased with the number of risk alleles (Ptrend<0.001). In-silico analysis showed that rs7514229, rs3181366 and rs2295800 polymorphisms may affect the transcription of mRNA by regulating miRNA binding, TF binding and promoter activation respectively, which may have biological consequences. Conclusion: TNFSF4-rs7514229, TNFSF8-rs3181366 and TNFSF8-rs2295800 are associated with increased risk of HCV infection in the Chinese high-risk population.